2016
DOI: 10.3233/cbm-150548
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of AKR1B10 in nasopharyngeal carcinoma as a potential biomarker

Abstract: AKR1B10 is overexpressed in nasopharyngeal hyperplasia, benign tumors, and carcinomas, being a potential new biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…In the present study, we have found that both AKR1B10 protein and mRNA levels were reduced in most of NPC tumors compared with para-carcinoma and benign tissues, which further suggests that AKR1B10 expression is down-regulated in the digestive tract cancers. He et al [ 32 ] also investigated that AKR1B10 expression levels in NPC tissues are lower than that in benign tissues, which is consistent to our results. However, in their studies, AKR1B10 expression levels are higher in NPC tissues than that in normal nasopharyngeal tissues of healthy people [ 32 ], which was not observed in our studies because it was too difficult to obtain normal nasopharyngeal tissues from healthy persons.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we have found that both AKR1B10 protein and mRNA levels were reduced in most of NPC tumors compared with para-carcinoma and benign tissues, which further suggests that AKR1B10 expression is down-regulated in the digestive tract cancers. He et al [ 32 ] also investigated that AKR1B10 expression levels in NPC tissues are lower than that in benign tissues, which is consistent to our results. However, in their studies, AKR1B10 expression levels are higher in NPC tissues than that in normal nasopharyngeal tissues of healthy people [ 32 ], which was not observed in our studies because it was too difficult to obtain normal nasopharyngeal tissues from healthy persons.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, AKR1B10 expression has been reported as an independent variable of favorable prognosis in 3 studies of colorectal, gastric, and nasopharyngeal carcinomas . It is of interests to note that He et al found AKR1B10 expression levels are higher in nasopharyngeal carcinoma (NPC) tissues compared with the normal nasopharyngeal tissues. In NPC tissues, AKR1B10 expression seemed high specifically in SCC, but low in basal cell carcinoma, adenoid cystic carcinoma, adenocarcinoma, and undifferentiated carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Elevated expression of AKR1B10 is found in a wide variety of human tumors, such as hepatocellular, 6,11,12 nonsmall cell lung, 13 breast, 14 cervical, 15 pancreatic, 16 and nasopharyngeal carcinomas. 17 Conversely, the expression of AKR1B10 is downregulated gastric, 18 colon, 19 and head and neck cancers. 20 AKR1B10 may exert disparate functions in tumorigenesis dependent upon the cellular context.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Elevated expression of AKR1B10 is found in nonsmall cell lung, hepatocellular, nasopharyngeal, cervical, pancreatic, and breast carcinomas. [8][9][10][11][12][13] Furthermore, it has been considered a valuable prognostic marker for hepatocellular, 9 cervical, 11 and breast 13 cancers. Recently, we demonstrated that a higher mean AKR1B10 labeling score, as assessed using immunochemical staining, is significantly associated with an advanced TNM classification and shorter survival in patients with OSCC.…”
Section: Introductionmentioning
confidence: 99%